MODELING THE PARAMETERS OF SOCIO-ECOLOGICAL AND ECONOMIC SUSTAINABLE DEVELOPMENT OF THE TERRITORY (ON THE EXAMPLE OF THE UNTSUKULSKY DISTRICT OF THE REPUBLIC OF DAGESTAN) - Zaur N. Ismikhanov; Gayirbeg M. Abdurakhmanov; Alimurad A. Gadzhiev; Madina G. Daudova; Raisat T. Radzhabova; Abdulgamid A. Teymurov; Yuliya Yu. Ivanushenko (Юг России: экология, развитие, 2018)
Abstract. Aim. To carry out scenario modeling of development of social and economic system of the Untsukulsky area of the Republic of Dagestan from positions of its stability. Material and methods. The work was based on data on the environmental and socio-economic development of the district, on the relationships of the main subsystems that form the socio-economic and environmental regional mechanism, the results of expert surveys, annual statistical reporting on the socio-economic development of the territory. Results. Cognitive maps of interrelations of basic parameters of ecological, social and economic development are constructed, the enlarged map of interrelations of social-economic and ecological subsystems of the Untsukulsky area is also constructed. The analysis of stability of socio-ecological-economic system of the territory. Scenario modeling of parameters of socio-ecological and economic development of the district is carried out. The results of the scenario modeling of the territory development showed that the regulatory role of the Federal center is an essential governing factor for the region in relation to its stability. The possibility of using scenario modeling for designing strategies for sustainable development of the territory on the basis of cognitive structurization of the development of possible situations is shown. Conclusion. The possibilities of cognitive structuring of knowledge about the problem situation are significant for the development of scenarios not only for a particular territory, but for the region in terms of its sustainability and design strategies based on them for the sustainable development of its socio-economic system. The most significant stage of the study of this problem is the collection of information, and its structuring in the form of a cognitive map.